The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5307/jbe.2015.40.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-dependent Physical Properties of Detarium microcarpum Seeds

Abstract: Purpose: Physical properties of Detarium microcarpum seeds were investigated as a function of moisture content to explore the possibility of developing bulk handling and processing equipment. Methods: Seed size, surface area, and 1,000-seed weight were determined by measuring the three principal axes, measuring area on a graph paper, and counting and weighing seeds. Particle and bulk densities were determined using liquid displacement and weight in a measuring cylinder, respectively. Porosity was computed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…Both static and dynamic friction coefficients for T. chebula dried fruit increased linearly with moisture content and varied with used structural surfaces. This trend was consistent with the findings of the previous studies (Aviara et al, 2014(Aviara et al, , 2015Shafaei et al, 2016).…”
Section: Static Coefficient and Dynamic Of Frictionsupporting
confidence: 93%
“…Both static and dynamic friction coefficients for T. chebula dried fruit increased linearly with moisture content and varied with used structural surfaces. This trend was consistent with the findings of the previous studies (Aviara et al, 2014(Aviara et al, , 2015Shafaei et al, 2016).…”
Section: Static Coefficient and Dynamic Of Frictionsupporting
confidence: 93%
“…It is also known by its traditional name, Abu Laila, in western Sudan. In Senegal, it is called dank; in Mali, it is called tamba dala [ 16 , 48 ]. To prevent infection, wounds can be treated with fresh bark or leaves, and the powder made from boiled bark can be used as a painkiller [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bark's infusion is said to have antiparasitic, diuretic, and anti-inflammatory properties, while the fruits and leaves are used to cure diarrhea and syphilis [ 34 ]. There are African tribes that use the fruit and leaves as a vegetable and as a seasoning for their food [ 16 , 48 ]. Diarrhea and syphilis can be treated with bark infusion, while dysentery and syphilis can be treated with fruits and leaves, respectively [ 12 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The variation in values may be as a result of the grinding of the sample. Aviara et al (2015), however, reported average values of 17.3 mm, 1316 kg m À3 , 653 kg m À3 , 3.184 kg,35%, and 58% for arithmetic mean diameter, particle density, bulk density, 1000-unit mass, porosity, and sphericity at a MC of 8.2% db. The differences are likely because of different moisture contents and different size composition of the experimental samples.…”
Section: Resultsmentioning
confidence: 90%